Effect on lifespan of high yield non-myeloablating transplantation of bone marrow from young to old mice - Kovina, Marina; Kagarlitskiy, German; Zuev, Viktor; Khodarovich, Yuriy (Frontiers in Genetics, 2013)
Tissue renewal is a well-known phenomenon by which old and dying-off cells of various tissues of the body are replaced by progeny of local or circulating stem cells (SCs). An interesting question is whether donor SCs are capable to prolong the lifespan of an aging organism by tissue renewal. In this work, we investigated the possible use of bone marrow (BM) SC for lifespan extension. To this purpose, chimeric C57BL/6 mice were created by transplanting BM from young 1.5-month-old donors to 21.5-month-old recipients. Transplantation was carried out by means of a recently developed method which allowed to transplant without myeloablation up to 1.5 × 108 cells, that is, about 25% of the total BM cells of the mouse. As a result, the mean survival time, counting from the age of 21.5 months, the start of the experiment, was +3.6 and +5.0 (±0.1) months for the control and experimental groups, respectively, corresponding to a 39 ± 4% increase in the experimental group over the control. In earlier studies on BM transplantation, a considerably smaller quantity of donor cells (5 × 106) was used, about 1% of the total own BM cells. The recipients before transplantation were exposed to a lethal (for control animals) X-ray dose which eliminated the possibility of studying the lifespan extension by this method.